History-Dependent Monetary Regimes: A Lab Experiment and a Henk Model - Jasmina Arifovic; Isabelle Salle; Hung Truong (Tinbergen Institute, 2023)
Price-level targeting (PLT) is optimal under the fully-informed rational expectations (FIRE) benchmark but lacks empirical support. Given the hurdles to the implementation of macroeconomic field experiments, we utilize a laboratory group experiment – where expectations are elicited from human subjects – to collect data on expectations, inflation and output dynamics under a traditional inflation targeting (IT) framework and a PLT regime with both deflationary and cost-push shocks. We then emulate the subjects' expectations with a micro-founded heterogeneous-expectation New Keynesian (HENK) model and reproduce the macroeconomic dynamics observed in the lab. Both in the lab and in the HENK model, the benefits of PLT over an IT regime obtained under the FIRE assumption are not observed: both human subjects and HENK agents are unable to learn the underlying implications of PLT, which results in excess macroeconomic volatility. However, once augmented with an inflation guidance from the CB consistent with closing the price gap, the stabilizing benefits of PLT materialize both in the lab and in the model.
Keywords: E7; E52; E42; C92; 330; heterogeneous expectations; learning; central bank communication; lab experiments